Morphology controlled ionothermal synthesis and characterization of ceria nanomaterials - Lee, Y.T. (Trans Tech Publications Ltd, 2014)
Crystalline ceria nanomaterials have been successfully synthesized through ionothermal treatment method. Morphology of the ceria nanoparticles are confirmed with scanning electron microscopy (SEM), transmission electron microscopy (TEM) with an average size of 6-30 nm, and with the N2 adsorption-desorption technique in the range of 46-62 m2/g in the presence of ionic liquid as base on acetate anion, trifluoroacetate anion, and dicyanamide anion as organic linker, cerium nitrate hexahydrate as precursor, and ammonia. It is found that the ceria synthesized by acetate anion based ionic liquid has cube shape morphology and gradually form belt shape as hydrothermal treatment temperature elevated. Ceria synthesized by trifluoroacetate anion based ionic liquid remains its cubic morphology even at elevated temperature. Whereas, ceria synthesized by dicyanamide anion based ionic liquid form irregular and agglomerate structures. Â© (2014) Trans Tech Publications, Switzerland.